The influence of currency risk upon the market value of commercial banks operating in the Polish banking sector - Zbigniew Korzeb (e-Finanse: Financial Internet Quarterly, 2015)
The objective of the paper is to analyse the impact of the Swiss National Bank's decision to introduce the floati ng exchange rate of the franc on January 15th, 2015, upon the market value of commercial banks operating in the Polish banking sector. The analysis involved twelve commercial banks quoted on the Warsaw Stock Exchange. The results are inconclusive. The predicted reduction of the banks' market value was less significant than indicated by market investors' reaction on the day after the announcement of the decision to introduce the floating exchange rate of the franc. The banks most prone to granting credit denominated in CHF did experience the largest reduction of their share quotations. However, the Pearson product-moment correlation coefficient calculated for the correlation between the average cumulative abnormal returns on shares for the entire analysed sample, and the proporti on of credits denominated in Swiss francs in the total credit portfolio, indicated only a moderate correlati on between both variables.
Keywords: G21; G14; G15; D81; 330; commercial banks; event studies; international financial markets; criteria for decision-making under risk and uncertainty